"The Distance … That Had Been Traversed": Education, Identity, and Public Literacy in Tara Westover's Educated and Richard Rodriguez's Hunger of Memory. (30th June 2022) - Blumberg, Ilana M.
Abstract: These two memoirs of American higher education represent higher education and advanced literacy as forces of social division, dividing their writers from their families and origins, and leaving unformulated a vision of higher education that might unify or elevate the American collective. Yet, the texts suggest a pedagogical possibility that life writing might serve as a via media between scholarship and popular writing that teacher-scholars might use to help our own students find in reflective education not only rupture and challenge, but also continuity and the possibility of return.